Upgrading Nature’s Tools: Expression Enhancement and Preparative Utility of the Halogenase RebH - Payne, James T.; Lewis, Jared C. (Synlett, 2014)
Enzymes often excel at performing green, selective chemical reactions, and thus offer key advantages over many chemocatalytic processes. We recently reported the enhanced expression of a regioselective halogenase, RebH, in E. coli, as well as its use in the preparative halogenation of a range of substrates. These improvements have made it possible to begin directed evolution to improve further the activity and substrate scope of RebH. Chemistry is in need of a regioselective halogenation catalyst, and this work illustrates the potential and recent gains made towards using enzymes for this goal.
Keywords: halogenation; catalysis; enzymes; directed evolution; protein engineering